Tinjauan Hukum Perdata terhadap Penahanan Ijazah dan Kebebasan Berkontrak Berdasarkan Pasal 1320 KUH Perdata - Suharti Jetia (Majelis: Jurnal Hukum Indonesia, 2025)
The practice of withholding a diploma as a condition of employment is still widespread in employment relationships in Indonesia. Generally, employers argue that withholding a diploma is intended to guarantee that workers complete the agreed-upon work contract period. However, this practice raises legal issues because it has the potential to violate the principle of freedom of contract, especially when viewed in light of the provisions of Article 1320 of the Civil Code (KUH Perdata), which regulates the conditions for a valid agreement. A diploma withholding clause can affect the fulfillment of the element of free agreement, because such clauses are often agreed to under duress or without fair alternatives for workers. This study aims to examine the validity of diploma withholding clauses in employment agreements and assess the legal consequences if such clauses are declared invalid. The research method used is a normative juridical approach by analyzing relevant laws and regulations, legal doctrine, and court decisions. The results of the analysis show that diploma withholding clauses often conflict with the conditions for a valid agreement, especially the element of lawful cause, because they conflict with the principles of protecting workers' rights and the principle of justice in freedom of contract. Furthermore, this practice can lead to human rights violations, considering that diplomas are important personal documents and cannot be confiscated without a clear legal basis. If the diploma retention clause is declared invalid, the clause is null and void and does not bind the parties. Consequently, the employer is obliged to return the diploma to the employee unconditionally, and the employee has the right to claim compensation if they suffer losses due to the retention. This study recommends the need for stricter regulations in employment regulations to prohibit the practice of diploma retention, in order to ensure the creation of fair and equal employment relationships in accordance with the principles of contract law.